Depressive Symptomatology and Quality Of Life in Idiopathic Parkinson's Disease Without Dementia. Preliminary Data From a New Scale Specifically to Assess Depression in Parkinson's Disease (2024)
To study the influence of depressive symptomatology and Quality of Life (QoL) in patients with Parkinson's Disease (PD) in Hoehn and Yahr stages I and II through a new scale that aims to measure depressive symptomatology specifically in PD. Depression is a neuropsychiatric pathology characterized by symptoms such as sadness, abulia, loss of appetite, sleep disturbances and low neurocognitive performance. It also affects dimensions related to QoL such as social stigma, cognition, activities of daily living, stigma and communication.